On the issue of the artistic casting production on an industrial scale - V. A. Emelyanov; O. V. Mikhailov; K. V. Martynov; S. S. Tkachenko (Литьë и металлургия, 2023)
The article presents an analysis of the formation parameters of the microrelief of artistic casting. The direction for solving particular issues of improving the castings quality with high requirements for the accuracy of the surface relief is shown.